1978
DOI: 10.1007/bf01136138
|View full text |Cite
|
Sign up to set email alerts
|

Fl�chtige Phenole in R�stkaffees verschiedener Sorten. I.

Abstract: Thirty phenols were isolated from roasted coffee by distillation-extraction, separated from other constituents by absorption-chromatography, and characterized by means of GC-MS. Robusta coffee contained the largest amount of phenols, followed by Arabusta (Côte d'Ivoire) and Arabica. Quantity and type of phenols depends on variety as well as on the roasting conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
1
6

Year Published

1981
1981
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 2 publications
0
10
1
6
Order By: Relevance
“…A variedade e a concentração dos compostos fenólicos voláteis no café torrado variam de acordo com o grau de torrefação e maiores quantidades, tanto com relação à variedade quanto à concentração, são detectadas em cafés submetidos à torrefação forte 9 . Outra informação interessante, é que o café da espécie robusta normalmente apresenta um perfil de compostos fenólicos mais rico do que o da espécie arabica (espécies consideradas de importância comercial atualmente) 9 . Dessa forma, fica claro que a distribuição desses compostos voláteis também depende da variedade do café.…”
Section: Fenóisunclassified
See 3 more Smart Citations
“…A variedade e a concentração dos compostos fenólicos voláteis no café torrado variam de acordo com o grau de torrefação e maiores quantidades, tanto com relação à variedade quanto à concentração, são detectadas em cafés submetidos à torrefação forte 9 . Outra informação interessante, é que o café da espécie robusta normalmente apresenta um perfil de compostos fenólicos mais rico do que o da espécie arabica (espécies consideradas de importância comercial atualmente) 9 . Dessa forma, fica claro que a distribuição desses compostos voláteis também depende da variedade do café.…”
Section: Fenóisunclassified
“…O fenol é observado com freqüência na fração volátil do café torrado, ao lado de metil-fenóis (ou cresóis) 4,[9][10][11][12][13][14][15][16] . O 2-metóxi-fenol (guaiacol) e seus derivados também foram descritos por vários autores 4,[9][10][11][12][13]17,18 .…”
Section: Fenóisunclassified
See 2 more Smart Citations
“…[1][2][3][4] Although hydrogen peroxide is used as a food additive for food processing in Japan, residual hydrogen peroxide in processed foods is not permitted owing to its possible carcinogenicity in mice. 5) 1,2,4-Benzenetriol (hydroxyhydroquinone) and related components are known to be present in roasted coffee beans, 6,7) and our previous study has demonstrated that 1,2,4-benzenetriol is a major hydrogen peroxide generating component causing DNA single strand breaks in vitro. 8) Although 1,2,4-benzenetriol is stable in a rather acidic brewed coffee, it generates 0.5-0.6 equimolar amounts of hydrogen peroxide in incubation under aerobic conditions at pH 7.4.…”
mentioning
confidence: 99%